Effectiveness of digital combined decongestive therapy for lower extremity lymphedema: a prospective single-arm clinical trial with follow-up - KOSTANOĞLU A.; Törpü G. C.; OTSAY S. (My University, 2026)
Purpose: This study aimed to investigate the effectiveness of digital combined decongestive therapy (CDT) in individuals with lower extremity lymphedema (LEL) and to determine its impact on limb volume and functional outcomes in short- and long-term follow-up. Materials and Methods: This prospective single-arm clinical trial with follow-up included individuals with LEL. Limb circumferences were recorded at baseline (V0), post-treatment (V1), and 12-week follow-up (V2). Functional status and participation were evaluated with the Lymphedema Functioning, Disability and Health Questionnaire for Lower Limb Lymphedema (LYMPH-ICF-LL). All participants received one weekly therapist-led CDT session over 4 weeks, supplemented by digitally guided self-management, followed by compression garment use during the follow-up phase. Results: Eighty-two patients with LEL (129 affected limbs; mean age 56.5 ± 18.3 years; 63 female/19 male; 47 bilateral/35 unilateral LEL; 37 primary/45 secondary LEL) were enrolled. Mean limb volume significantly decreased from 5027.7 ± 1826.0 mL at baseline to 4682.3 ± 1746.0 mL post-treatment (p < 0.001), and further to 4310.5 ± 1380.2 mL at follow-up (p < 0.001). Improvements were also observed in total and domain-specific LYMPH-ICF-LL scores at both time points (all p < 0.001). Conclusions: Digital CDT reduces extremity volume and improves functionality in LEL patients, demonstrating short and long-term efficacy. It provides an alternative to conventional CDT, enhancing accessibility and adherence.
Keywords: Tıp; Dahili Tıp Bilimleri; Fiziksel Tıp ve Rehabilitasyon; Sağlık Bilimleri; Medicine; Internal Medicine Sciences; Physical Medicine and Rehabilitation; Health Sciences; Klinik Tıp (Med); Klinik Tıp; Rehabilitasyon; Clinical Medicine (Med); Clinical Medicine; Rehabilitation; combined decongestive therapy; digital physiotherapy; Lower extremity lymphedema; quality of life; self-management